Numerical Computation of Maximum Shear Stress Intensity for a Nearly Circular Crack Subject to Shear Loading - Feng, Koo Lee; Nik Long, Nik Mohd Asri; Zainidin K, Eshkuvatov; Jin, Wong Tze (Journal of Science and Technology, 2012)
Maximum shear stress intensity for nearly circular cracks subjected to equal and opposite shear stresses are considered. A hypersingular integral equation containing the crack opening displacement is formulated. Conformal mapping technique is employed to transform the obtained hypersingular equation into a similar equation over a circular crack. A suitable collocation points are chosen to reduce the hypersingular integral equation into a system of linear equations. Numerical solution of the linear equations and the corresponding maximum shear intensity is obtained and presented graphically. Our results seem to agree with the existing asymptotic solution.